Hypofractionated volumetric‐modulated arc therapy for breast cancer: A propensity‐score‐weighted comparison of radiation‐related toxicity. Issue 1 (8th March 2021) - Kim, Nalee; Chang, Jee Suk; Shah, Chirag; Shin, Hyejung; Keum, Ki Chang; Suh, Chang‐Ok; Kim, Yong Bae
Abstract: We assessed the clinical benefit of combining volumetric‐modulated arc therapy (VMAT) and hypofractionated radiotherapy (HF‐RT) considering the incidence of radiation‐related toxicities. After a retrospective review for breast cancer patients treated with adjuvant RT between 2005 and 2017, a total of 4209 patients treated with three‐dimensional conventional fractionation (CF‐3D, 50.4 Gy/28 fractions) and 1540 patients treated with HF‐RT (768 received HF‐3D; 772, HF‐VMAT; 40 Gy/15 fractions) were included. A total of 2229 patients (38.8%) received regional node irradiation (RNI): 1642 (39.0%), 167 (21.7%) and 420 (54.4%) received RNI via CF‐3D, HF‐3D and HF‐VMAT, respectively. Acute/subacute and late toxicities were evaluated. Propensity scores were calculated via logistic regression. Grade 2+ acute/subacute toxicities was the highest in CF‐3D group (15.0%, 2.6% and 1.6% in CF‐3D, HF‐3D and HF‐VMAT, respectively; P < .001). HF‐VMAT reduced Grade 2+ acute/subacute toxicities significantly compared to CF‐3D (odds ratio [OR] 0.11, P < .001) and HF‐3D (OR 0.45, P = .010). The 3‐year cumulative rate of late toxicities was 18.0% (20.1%, 10.9% and 13.4% in CF‐3D, HF‐3D and HF‐VMAT, respectively; P < .001). On sensitivity analysis, the benefit of HF‐VMAT was high in the RNI group. Acute and late toxicities were fewer after HF‐VMAT than after HF‐3D or CF‐3D, especially in women who underwent RNI. Abstract : What's new? Hypofractionated radiotherapy (HF‐RT) is increasingly used for whole breast irradiation. However, concerns of possible radiation‐related toxicities persist. Here, in a cohort of breast cancer patients treated with adjuvant RT, the clinical benefits of intensity‐modulated RT (IMRT) with HF were compared with three‐dimensional conventional fractionation (CF‐3D), HF‐3D, and HF volumetric‐modulated arc therapy (HF‐VMAT). Compared to CF‐3D and HF‐3D, a three‐week schedule of 40 Gy in 15 fractions of HF‐VMAT had the lowest rate of radiation‐related acute and late toxicities. HF‐VMAT also had fewer subacute toxicities. The findings indicate that HF‐VMAT can significantly benefit breast cancer patients treated with regional node irradiation.